HUMAN LEUKOCYTE ANTIGEN (HLA) GENE IN DENGUE INFECTION - Ety Apriliana (Fakultas Kedokteran Universitas Lampung, 2014)
The geographic distribution of the Dengue Virus (DENV) and the incidence of the viral infection have grown fast in recent decades, and dengue fever is considered to be one of the most important reemergent tropical diseases. The majority of dengue infections are subclinical; however, the clinical manifestations of dengue infection range from the benign, self-limited Dengue Fever (DF) to a vasculopathy syndrome known as Dengue Hemorrhagic Fever (DHF) that can lead to hypovolemic Dengue Shock Syndrome (DSS). Several epidemiological studies indicated that genetic factors constitute important components in disease susceptibility. Several human HLA class I and II alleles are associated with development of DHF. The human leukocyte antigen alleles have been implicated as probable genetic markers in predicting the susceptibility and/-or protection to severe manifestations of DENV infection. [JuKe Unila 2014; 4(8):240-244]